ROLE OF OFFSHORE JURISDICTIONS IN THE FOREIGN ECONOMIC ACTIVITY OF THE RUSSIAN COMPANIES - Y. Grigoryeva (Вестник университета)
The impact offshore to the Russian economy began to develop because of the adverse investment climate in the country. This article is devoted to the analysis of problems of use of offshore jurisdictions in the foreign economic relations of Russia. Benefits and problems of use by entrepreneurs of offshore schemes are revealed.